(untitled) (Південний архів (історичні науки), 2023)
This article analyzes the process of supporting the team of the West Baltic countries (Lithuania, Latvia and Estonia) after they regained their independence and implemented the joint efforts of these “Baltic sisters” towards the EU and NATO. The article contains specific programs, according to which there is an approach to the Western course of the Baltic states to the membership of international organizations. In the study, the results of the amount of aid provided to the three Baltic countries by their Western partners. The purpose of the article is to analyze the process of supporting the collective West of the Baltic states in the first summer of their restoration of independence. During the conduct of this study, the following methods were used: historical and comparative, analysis, synthesis and dynamics. The results. This article states that the Baltic states, after regaining their independence, took a strategic course to the west and refused to interact politically with the eastern blocs. This course for the Baltic countries was to acquire full membership in the EU and NATO. moreover, the Western countries tried not only ideologically to support such a foreign policy aspiration of the Baltic peoples, but also economically. In addition, the neighboring Western states took a direct part in the privatization processes and contributed to the appearance of significant investments in the Baltic countries. It was especially important in the first years of independence, in the conditions of the crisis of the transition from a planned to a market economy. In the security aspect, the USA played an important role, which provided substantial assistance with its support programs in the three Baltic countries, especially during the movement of the latter to NATO. Such mutual aspirations on the part of the USA and a number of European countries, especially Finland, Sweden, Germany and Poland contributed to the fact that the three Baltic states simultaneously became full members of NATO and the EU in 2004. Conclusions. Therefore, support from the West during a difficult and important period for the three Baltic countries, which took place in the conditions of political and economic transformation, did not go unnoticed by the West. The latter made significant efforts to help these post-Soviet states become full participants in the Western world, as they were before their occupation by the USSR.